Conducta socio-afectiva en el transtorno autista: descripción e intervención psicoeducativa - López Gómez , Santiago (2022)
Autistic disorder refers to a neuropsychological disorder with serious and heterogeneous manifestations that include three main areas of development, namely: social and affective alterations, alterations in the linguistic and communicative behaviour and the presence of behavioural patterns, interests or restricted and stereotyped activities. The failure that affects the maintenance and development of social and affective bonds, characterized by social isolation and the presence of inadequate behaviours of social-affective interactions, is highlighted in the social and affective dimension. At the present time, the most effective way to treat autism is by means of psycho-educative programs. The main characteristics of the disorder, emphasizing the social-affective area, are presented, together with generic lines of intervention consider from the psycho- educative perspective.